Multi-acid synergistic fermentation enhances the quality of bran feed - Pan, Wanshu; Li, Binbin; Chong, Kah Hui; Wang, Song; You, Ling; Wang, Xin; Nor-Khaizura, Mahmud Ab Rashid; Mustapha, Nor Afizah; Saari, Nazamid; Wan Ibadullah, Wan Zunairah (Frontiers in Microbiology, 2025)
IntroductionThe production of Nongxiangxing Baijiu (Chinese liquor) involves a complex interplay of microbial community metabolism and multi-microbial co-fermentation. The Nongxiangxing Baijiu pit mud is rich in anaerobic acid-producing microorganisms, and this study was designed to investigate the impact of multi-acid synergistic fermentation on feed quality.MethodsThree Nongxiangxing Baijiu pit muds were subjected to selective serial passage (SSP) three times with four different media (GM, LM, GY, and LY). All samples fermented in GM exhibiting more microbial growth and higher total titratable acidity. Microbial composition analysis of these samples revealed the presence of three acid-producing microbiota (GMAS2, GMBS3, and GMCS3) which were then selected for bran fermentation with three times of SSP.ResultsThe bran fermented with acid-producing microbiota was rich in Pediococcus and Lactobacillus and exhibited increased total titratable acidity and organic acid levels. Electronic nose and organic acid composition analysis revealed that GMAS2S3 (bran fermented with GMAS2 that underwent three times of SSP) had more pronounced flavor characteristics and a higher abundance of acids. Proximate and amino acid analyses confirmed that GMAS2S3 had a higher protein content (22.8%) than the conventional feed (22.8% vs. 16–18%) with abundant amino acids (229.41 mg/g). Palatability evaluation analysis revealed that GMAS2S3-supplemented groups initially showed significantly lower feed intake than the basal diet group, but exceeded basal diet intake during the later adaptation phase.DiscussionIn conclusion, multi-acid synergistic fermentation using anaerobic acid-producing microbiota from baijiu pit mud enhanced bran feed nutritional quality and organic acid content, while maintaining palatability, paving a way for a cost-effective alternative animal feed.